Computational Evaluation of ADMET Properties and Molecular Docking Studies on Cryptolepine Analogs as Inhibitors of HIV Integrase - Gupta, Rajeev; Raza, Amir; Singh, Shivam Kumar; Kaur, Jasmeen; Wadhwa, Pankaj (Current Signal Transduction Therapy, 2025)
BackgroundHIV/AIDS remains a global health challenge, demanding innovative antiretroviral strategies. HIV integrase inhibition, a promising therapeutic target, warrants exploration. This study investigates the potential of Cryptolepine and analogues as integrase inhibitors through in-silico docking and ADMET profiles. Docking simulations reveal binding affinities, guiding rational drug design. ADMET predictions assess the pharmacokinetics, ensuring clinical viability. Cryptolepine and analogues show promise, offering a pathway for therapeutic development against HIV/AIDS. Further, insights contribute to ongoing efforts in combating the pandemic with effective antiretroviral strategies.MethodsMolecular docking investigations utilized Molegro Virtual Docker (MVD) 6.0, with the target protein [PDB ID: 1QS4] obtained from the Protein Data Bank. Ligands, particularly Cryptolepine-based, were selected from PubChem with adherence to Lipinski's Rule of Five for drug-like properties. Computational tools, including pkCSM, aided ADMET profiling. This study, conducted on an AMD Ryzen 3 3200U computer with Windows 10 home, enhances understanding and potential therapeutic strategies against HIV/AIDS.ResultsFrom a virtual screening of the PubChem database, the top ten candidates were selected based on their MolDock scores against the target 1QS4. All compounds had MolDock scores greater than -70.00 kcal, with [01] RPA 1 exhibiting the highest MolDock Score (-83.85 kcal) and Rerank Score (-39.59 kcal). These compounds possessed the essential pharmacophore for HIV integrase inhibition against 1QS4. However, three compounds, including [01] RPA 1, [00] RPA 1_6, and [04] RPA 1_1, showed no hydrogen bonding interactions with Val 79 and Val 150 amino acid residues. This highlights the importance of structural analysis in understanding ligand-receptor interactions for rational drug design against HIV integrase.ConclusionThis study investigates how Cryptolepine analogues inhibit HIV integrase via docking and ADMET analysis. All analogues exhibit strong binding, especially those within the 400-500 Da range. Specific amino acids and hydrogen bonds influence interactions. Compound [01] RPA 1_3 shows high intestinal absorption and promising properties, making it a potential HIV integrase inhibitor. The study highlights the importance of a comprehensive ADMET profile in drug development and suggests further exploration of [01] RPA 1_3 for HIV/AIDS therapy.
Keywords: binding affinity